Parental Involvement and Self-Regulation of School Juvenile Delinquency - Miranti Rasyid; Niecen Normillah (Universitas Pendidikan Ganesha, 2022)
The phenomenon of promiscuity at this time is very rife and quite familiar to us, especially currently that have developed. This study aims to analyses parental involvement effect with also self-regulation on juvenile delinquency in Senior High School students. This research method uses a quantitative approach. The subject of this study were 108 Senior High School students in total who were selected using probability sampling techniques with random sampling. Data collection methods used were juvenile delinquency scale, parental involvement, and self-regulation. SPSS software is used (with inferential statistical approaches and descriptive) for analyzing data’s that are collected. The results showed that: there was a significant effect of parental involvement and self-regulation on juvenile delinquency in Senior High School students. There is also found a significant effect of parental involvement on juvenile delinquency in Senior High School students. And there is found a significant effect self-regulation on juvenile delinquency in Senior High School students with the beta coefficient.